Self‐Driven Perovskite Narrowband Photodetectors with Tunable Spectral Responses. Issue 3 (9th December 2020) - Wang, Jian; Xiao, Shuang; Qian, Wei; Zhang, Kai; Yu, Jun; Xu, Xiuwen; Wang, Gaopeng; Zheng, Shizhao; Yang, Shihe
Abstract: Narrowband photodetectors with tunable spectral responses are highly desirable for applications in image sensing, machine vision, and optical communication. Herein, a filterless and self‐driven perovskite narrowband photodetector (PNPD) based on the defect‐assisted charge collection narrowing (CCN) mechanism is reported, which is enabled by a high‐quality thick perovskite film. By adjusting the halide component of the perovskite layer, the bandgap is successfully modulated and the corresponding narrowband photodetectors show a wide spectral response range from the red to the near‐infrared (NIR), all with full‐widths at half maximum (FWHMs) below 30 nm. Specifically, the methylammonium lead iodide (MAPbI3 ) narrowband photodetector exhibits a characteristic detection peak at 800 nm with a very low noise current of ≈0.02 pA Hz –1/2, a high specific detectivity up to 1.27 × 10 12 Jones, and a fast response speed with rise/fall time of 12.7/6.9 µs. Impressively, these values are among the highest of their kind reported previously, and allow demonstration of narrowband imaging. The excellent performance of self‐driven PNPDs lights up their prospect in high‐efficiency optoelectronic devices without external power sources. Abstract : Filterless and self‐driven charge‐collection‐narrowing (CCN)‐type perovskite narrowband photodetectors are fabricated with tunable spectral responses from the red to the near‐infrared (NIR) region. Specifically, the MAPbI3 ‐based narrowband photodetector exhibits remarkable performances at 800 nm, with full‐width at half maximum less than 30 nm, which are comparable to the highest reported values, allowing the successful demonstration of narrowband imaging.